THE EFFECT BETWEEN INTEREST LEARNING AND DISCIPLINE LEARNING TOWARD THE RESULT OF LEARNING MATHEMATICS STUDENT - Ratih Dian Utami; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The purpose of the study to determine whether there is an effect between interest learning and discipline learning toward the result of learning mathematics students. The population in this research are students of class VII Muhammadiyah Junior High School 1 Gamping (SMP Muhammadiyah 1 Gamping) school year 2016/2017 as the sample is two classes. The technique of using random sampling. The technique of interpretation of the data is questionnaires and tests. Data analysis technique with 5% significant level obtained: (1) the effect of interest learning toward the result of learning mathematics student with FA = 36,304 as well as high learning interest more effect toward the result of learning mathematics student with tA = 4,2317, (2) the effect of discipline learning toward the result of learning mathematics student with FB = 10,23 and high learning discipline did not affect the result of learning mathematics student with tB = 1,605, (3) the effect between interest learning and discipline learning toward the result of learning mathematics student with FC = 28,94 interest High learning combined low discipline of learning equals low learning interest combined with high learning discipline with LSD = 7,363 and high learning interest combined low learning discipline similar to low learning interest combined high discipline learning with LSD = 7,613.